Linguistic Twists and Moral Decay in The Creative Arts of Contemporary Society (Integral Research, 2025)
The creative arts, of which literature is a part, have been an integral part of human culture since the evolution of man. Apart from literature, the creative arts also include theatre/films, music, painting, sculpturing, to mention but a few. Through the creative arts, man’s great achievements, his passions and struggles, his belief system and general ways of life, and his moments of disappointments and conquests have not only been documented but have also been preserved for society even before man developed a formal channel of documentations. This perspective paper explores the multifaceted impact of the aberration of language on culture, probing into its role in shaping societal values. Drawing from virtue ethics, discourse analysis and cultural studies, this paper analyzes various creative art forms, including literature, film, and music. It examines how creative expression can challenge the status quo, inspire innovation, and enrich the human experience. It also probes into the intricacies of contemporary creative writing, artistic activities, the language of artists and its significance to society.  It discusses the role of literature and other art forms in society, focusing on the African context, and particularly Nigeria. It critiques issues of nudity, sexualization and vulgarity in contemporary Nigerian films and music, arguing that these undermine societal values. Given the rapid changes in society, the study argues that artists need to adapt their works to address the challenges of the modern world, ensures the sustainability of the African identity, particularly Nigerian cultural identity as well as safeguard the age-long environmental wisdom.
Keywords: Creative Arts, Innovations, Language, Literature, Nigeria, Society.